Utilizing case study to understand elementary geometry: A practical approach - Hantoro Ksaid Notolegowo (Journal of Science and Science Education, 2018)
In contrast to the branches of mathematics in general that require only analytical skills through formula calculation, geometry requires other skills in the form of visual ability to understand. The student's analytical skills can be enhanced by theoretical learning methods. However, theoretical learning method will not be optimal in improving the visual ability. Another method is required that can encourage students' analytical and visual abilities. The learning method that suits these needs is a case study. The case study method in geometry lessons can be applied by creating scenarios that are divided into two stages: the preparation stage and the implementation stage. The preparation stage is related to the formulation of scenarios of case studies that will be conducted by the students in the field, while in the implementation stage the students conduct direct observation in the field based on the case study scenario at the preparation stage and then present the observation result through the presentation, accompanied by suggestion and evaluation from teachers.